Stochastic Modeling to Make Efficient Use of Public Transportation - Pratama, Yohanssen (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Recently in Indonesia appeared a new breakthrough in terms of public transport, namely online taxi that can be ordered online via smartphone or mobile telephone. This phenomenon raises some effects to the community, one of the negative effects is the income of conventional public transport drivers (commonly referred as angkot drivers) were drastically reduced. This already caused some clashes between the online taxi drivers and angkot drivers. To maintain the income of angkot drivers we need to build a management system that can provide some information to the drivers. The sufficient time to pick up passengers and how the system will provide many units of vehicles on the specific route that should operate. A stochastic is proposed a model to become a base for an information system that provides some outputs to help the angkot drivers and the transportation agencies make a right decision.